Peran Lingkungan Keluarga dalam Pembentukan Perkembangan Sosioemosional: Sebuah Tinjauan Literatur - Viga Fatimah Tuazzara; Mega Kencana; Suci Fajrina (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Children's socio-emotional development is an important aspect that plays a role in their ability to recognize, understand, express, and regulate emotions, as well as interact adaptively in social environments. The family serves as the first environment that provides the foundation for this development through parenting patterns, emotional relationships, daily interactions, and parental behavior models. This study uses the Systematic Literature Review (SLR) method by analyzing scientific articles published between 2020–2025 from the Scopus, ERIC, ScienceDirect, and Google Scholar databases. The results of the review indicate that parental responsiveness, observational learning, secure attachment, and emotional communication significantly influence children's emotion regulation and social skills. In addition, parenting styles, particularly the authoritative style, have been shown to have a positive impact on psychological well-being, self-control, and social competence, while authoritarian, permissive, and neglectful styles are associated with behavioral problems and low self-esteem. Overall, the quality of the family environment and patterns of emotional communication play a significant role in shaping children's socio-emotional development. These findings underscore the need for support and reinforcement of parenting practices in efforts to enhance children's emotional and social well-being.